IMPLEMENTASI MODERASI BERAGAMA SEJARAH MULTIKULTURAL AGAMA DI DESA BULU LOR JAMBON PONOROGO - Ngadhimah, Mambaul; Aulia, Naja; Ayu, Diah; Taufiqul, Muhammad; Satria, Fais (Proceedings of Annual Conference on Community Engagement, 2023)
The philosophy of multiculturalism acknowledges the different variations that people, groups, and society have about values, systems, culture, religion, social interactions, and politics. One of these is multiculturalism, which distinguishes between the beliefs, practices, rituals, and values of certain communities that practice multiple religions, such those in Bulu Lor Village, Jambon, and Ponorogo. Their people can live side by side in harmony, peace, tolerance, and mutual understanding since they follow both Buddhism and Islam. Religious diversity frequently breeds limited fanaticism, which in turn causes conflict in people’s lives, discord, and the disintegration of society norms and values. The goal of this study is to document the historical introduction of Buddhism and Islam in order to promote religious moderation. With the stages of Appreciative Inquiry, Community Mapping, Transect, Association Mapping and Design Intuition, Individual/Inventory Skill, Leacky Bucket, and Low Hanging Fruit, this community service strategy follows the Asset Based Community Development (ABCD) methodology. The implementation of religious moderation in this community service program has resulted in a decades-long multicultural heritage of Buddhism and Islam in Bulu Lor Village. This history is mirrored in the cooperative, tolerant, safe, and peaceful society that exists inside the program. Strong religious tolerance that does not quickly erode across generations is based on the histories of the top-down entry of Buddhism and the natural entry of Islam. In order to create a calm, secure, and peaceful society, moderate religious practice is crucial.